Q: What is 3x -2y 7 3x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x plus 2y can be expressed mathematically as (3x + 2y).

3x + 2y = 7

3x-2y-7=0

Standard form is: y = Mx + b so you must solve for y 3x = 2y + 7 3x - 7 = 2y 2y = 3x - 7 y = ( 3 / 2 )x - ( 7 / 2 )

If: 3x+2y = 5x+2y = 7 which is the same as 7 = 7 = 7 Then: 3x+2y = 7 and 5x+2y = 7 Subtracting equations: x = 0 Therefore by substitution: x = 0 and y = 3.5

Related questions

3x plus 2y can be expressed mathematically as (3x + 2y).

3x = 2y + 7 The standard form is: 3x - 2y - 7 = 0

3x + 2y = 7

3x+2y-7=0 2y=-3x+7 y=1/2(-3x+7) or -3/2 x +7/2

3x-2y-7=0

Standard form is: y = Mx + b so you must solve for y 3x = 2y + 7 3x - 7 = 2y 2y = 3x - 7 y = ( 3 / 2 )x - ( 7 / 2 )

If: 3x+2y = 5x+2y = 7 which is the same as 7 = 7 = 7 Then: 3x+2y = 7 and 5x+2y = 7 Subtracting equations: x = 0 Therefore by substitution: x = 0 and y = 3.5

If: 3x+2y = 5x+2y = 7 Then: 3x+2y = 7 and 5x+2y = 7 Subtract the 1st equation from the 2nd equation: 2x = 0 or x = o By substitution: x = 0 and y = 3.5

3x+2y=20 5x-2y=1 (3x+2y) + (5x-2y)= 20+1 3x+5x= 21....... 8x=21.........x=2 5/8 Subsitute x=3(2 5/8)+ 2y=20........... 7 7/8 +2y=20.........2y= 20- 7 7/8....... y=6 1/16

Combine like terms. 6x - 2y +7.

3x - 2y + 7x + 4y = 3x + 7x - 2y +4y = (3+7)x + (-2+4)y = 10x + 2y

3x - 2y and 3x + 2y are in their simplest form. They don't factor.